'Managing patient involvement': provider perspectives on diabetes decision‐making. (7th June 2011) - Shortus, Tim; Kemp, Lynn; McKenzie, Suzanne; Harris, Mark
Abstract Background Most studies of shared decision‐making focus on acute treatment or screening decision‐making encounters, yet a significant proportion of primary care is concerned with managing patients with chronic disease. Aim To investigate provider perspectives on the role of patient involvement in chronic disease decision‐making. Design A qualitative, grounded theory study of patient involvement in diabetes care planning. Setting and participants Interviews were conducted with 29 providers (19 general practitioners, eight allied health providers, and two endocrinologists) who participated in diabetes care planning. Results Providers described a conflict between their responsibilities to deliver evidence‐based diabetes care and to respect patients' rights to make decisions. While all were concerned with providing best possible diabetes care, they differed in the emphasis they placed on 'treating to target' or practicing 'personalized care'. Those preferring to 'treat to target' were more assertive, while 'personalized care' meant being more accepting of the patient's priorities. Providers sought to manage patient involvement in decision‐making according to their objectives. 'Treating to target' meant involving patients where necessary to tailor care to their needs and abilities, but limiting patient involvement in decisions about the overall agenda. 'Personalized care' meant involving patients to tailor care to patient preference. Discussion and conclusions Respecting a patient's autonomy and delivering high‐quality diabetes care are important to providers. At times it may not be possible to do both, so a careful balance is required. Involving patients in decision‐making may be a means to this end, rather than an end in itself.